Towards greener transport and sustainable travel behaviour : the case of the South African government vehicle fleet - Sehlodimela, Khutjo Lekgwareng (Stellenbosch : Stellenbosch University, 2022)
Thesis (MCom)--Stellenbosch University, 2022.